2021
DOI: 10.1002/jwmg.22099
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Movements: Shifts in Calving Area Selection by Partially Migratory Elk

Abstract: Loss of migratory behavior or shifts in migratory ranges are growing concerns to wildlife managers. How ungulates prioritize safety from predators at the expense of high‐quality foraging opportunities during calving may be key to understanding these shifts and long‐term reproductive success. We compared trade‐offs in selection for forage and predation risk by elk (Cervus canadensis) following 3 migratory tactics (western and eastern migration and resident) during 2 time periods in a declining (by almost 70% fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 110 publications
(167 reference statements)
2
44
0
Order By: Relevance
“…Evidence that a scat-based approach can describe broad-scale patterns of predation risk is supported by the correspondence be- (Berg et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Evidence that a scat-based approach can describe broad-scale patterns of predation risk is supported by the correspondence be- (Berg et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…The study area encompassed the summer range of the partially migratory Ya Ha Tinda elk herd along the eastern slopes of the Rocky Mountains in and adjacent to Banff National Park (Figure 1 ). The Ya Ha Tinda elk herd has declined by 70% from ~1400 elk counted in 2002 to ~450 elk in 2016 (Berg et al, 2021 ). Historically, over 90% of the elk population migrated ~50 km west from the Ya Ha Tinda winter range into Banff National Park.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parturition events can be monitored in real time for studies involving the capture of neonates (Figure 2; Obermoller et al, 2019), or events can be identified post-hoc for retrospective analyses of ungulate breeding and fecundity (Bonar et al, 2018;Long et al, 2009). Previous studies have used piecewise regression to identify change points indicative of ungulate parturition based on movement, but implementation of the mcp package can provide additional analytical options (Berg et al, 2021).…”
Section: Pre-parturition Movementmentioning
confidence: 99%